2020
DOI: 10.1111/lam.13389
|View full text |Cite
|
Sign up to set email alerts
|

Eleutheroside K isolated from Acanthopanax henryi (Oliv.) Harms suppresses methicillin resistance of Staphylococcus aureus

Abstract: Acanthopanax (A.) henryi (Oliv.) Harms contain many bioactive compounds commonly used in traditional Chinese medicine. The objective of the present study was to investigate the antibacterial activity of the single constituent, Eleutheroside K (ETSK) isolated from the leaves of A. henryi (Oliv.) Harms, against methicillin‐resistant Staphylococcus (S.) aureus (MRSA). Broth microdilution assay was used to measure the minimal inhibitory concentration (MIC) and the MIC values of ETSK against eight clinical S. aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…There are few studies on the pharmacological activity of ETSK. By determining the antibacterial susceptibility, our previous studies confirmed the pharmacological mechanism of ETSK reversing the methicillin resistance caused by MRSA and displayed a minimal inhibitory concentration of 50 µg/mL [ 24 ]. In this context, the antibacterial ability of ETSK will be further investigated by analyzing the effect of ETSK on the secretion of staphylococcal virulence factors in vitro.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…There are few studies on the pharmacological activity of ETSK. By determining the antibacterial susceptibility, our previous studies confirmed the pharmacological mechanism of ETSK reversing the methicillin resistance caused by MRSA and displayed a minimal inhibitory concentration of 50 µg/mL [ 24 ]. In this context, the antibacterial ability of ETSK will be further investigated by analyzing the effect of ETSK on the secretion of staphylococcal virulence factors in vitro.…”
Section: Introductionmentioning
confidence: 79%
“…Real-time RT-PCR was performed as previously described [ 26 ]. In our previous experiment, it has been determined that the minimum inhibitory concentration of ETSK against ATCC 33,591 is 50 µg/mL [ 24 ]. The ATCC 33,591 strain was grown to an absorbance value of 0.9 at an optical density 600 nm (OD 600nm ) and treated with sub-inhibitory concentrations (6.25–25 µg/mL) of ETSK for 4 h [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The main glycosides are Acanthopanax glycosides A, B, C, D, E, F, and G. Polysaccharides mainly include glucose, sucrose, alkali-soluble polysaccharide and water-soluble polysaccharide. Fatty acids and quinones mainly include methyl oleate, ethyl oleate, 10, -octadecadienoic acid, 10, -octadecadienoic acid, ethyl ester, mymyritic acid, palmitic acid, 9, 11-octadecadienoic acid, hexadecadienoic acid ( Li et al, 2021 ).…”
Section: Molecular Mechanism Of Action Of Sg Antidepressantsmentioning
confidence: 99%
“…Rosin (34) and eugenol glucoside (43) were isolated from fruits and flowers of AH, respectively [12,21]. Ferulic acid (35), syringin (37), and trans-coniferin (38) have been obtained from the roots of AH [19]. Meanwhile, trans-p-hydroxycinnamic acid (39), (E)-caffeic acid methyl ester (40), trans-coniferyl aldehyde (41), and trans-sinapaldehyde (42) were retrieved from the stem part of this plant [20].…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…Moreover, one latest study reported that another pentacyclic triterpenoid saponin, Eleutheroside K (20), isolated from the leaves of AH, can effectively inhibit the growth of MRSA through down-regulating the expression of PBP2a [35].…”
Section: Antimicrobial Activitymentioning
confidence: 99%